Pengaruh Sertifikasi dan Standardisasi Produk terhadap Peningkatan Penjualan dan Daya Saing UMKM - Anita, Nur; Iznillah, Muhammad Luthfi (Akuntansi & Ekonomika, 2023)
This study aims to examine the effects of product certification and standardization on the increase in sales and competitive advantages of MSMEs. This study uses a quantitative method with a sample of 52 SMEs assisted by CSR PT Pertamina RU II Sei Pakning. The results showed that partial certification had a positive effect in increasing the competitiveness of MSMEs. While standardization has a positive influence on sales and the competitiveness of MSMEs, certification and standardization together have a positive and significant impact on increasing sales and the competitive advantages of SMEs. This research is important because it provides both conceptual and empirical evidence regarding the role of certification and standardization in increasing sales and competitiveness of MSMEs. Thus, this research can be a reference for the follow-up of MSMEs in the future to survive in the long term.